Molecular Dynamics Analysis of Charge Transport in Ionic‐Liquid Electrolytes Containing Added Salt with Mono, Di, and Trivalent Metal Cations. Issue 13 (18th April 2018) - Vicent‐Luna, José Manuel; Azaceta, Eneko; Hamad, Said; Ortiz‐Roldán, José Manuel; Tena‐Zaera, Ramón; Calero, Sofía; Anta, Juan Antonio
Abstract: Among many other applications, room‐temperature ionic liquids (ILs) are used as electrolytes for storage and energy‐conversion devices. In this work, we investigate, at the microscopic level, the structural and dynamical properties of 1‐methyl‐1‐butyl‐pyrrolidinium bis(trifluoromethanesulfonyl) imide [C4 PYR] + [Tf2 N] − IL‐based electrolytes for metal‐ion batteries. We carried out molecular dynamics simulations of electrolytes mainly composed of [C4 PYR] + [Tf2 N] − IL with the addition of M n+ ‐[Tf2 N] − metal salts (M=Li +, Na +, Ni 2+, Zn 2+, Co 2+, Cd 2+, and Al 3+, n=1, 2, and 3) dissolved in the IL. The addition of low salt concentrations lowers the charge transport and conductivity of the electrolytes. This effect is due to the strong interaction of the metal cations with the [Tf2 N] − anions, which allows for molecular aggregation between them. We analyze how the conformation of the [Tf2 N] − anions surrounding the metal cations determine the charge‐transport properties of the electrolyte. We found two main conformations based on the size and charge of the metal cation: monodentate and bidentate (number of oxygen atoms of the anion pointing to the metal atoms). The microscopic local structure of the M n+ ‐[Tf2 N] − aggregates influences the microscopic charge transport as well as the macroscopic conductivity of the total electrolyte. Abstract : Monodentate and bidentate conformations of [Tf2 N] − anions solvating metal cations are identified by molecular dynamics simulations. The occurrence of one or the other is a consequence of the size and charge of the cations. The local arrangement of ions is found to have a key influence on the conductivity of the electrolyte.